2018
DOI: 10.1021/acs.inorgchem.8b01579
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Oxidized Zinc(II) Phthalocyanine Cations: Structure, Spectroscopy, and Decomposition Behavior

Abstract: A bromonium oxidizing agent was used to produce a ring-oxidized zinc phthalocyanine (PcZn), [PcZn(solvent)][BAr] (1·solvent), in good yield. This material is dimeric in the solid state with one axially coordinated solvent [tetrahydrofuran (THF) or 1,2-dimethoxyethane (DME)] and close intradimer ring-ring distances of 3.18 and 3.136 Å (THF and DME respectively); this proximity facilitates strong antiferromagnetic coupling to yield diamagnetic dimers. 1·THF is present in solution as a monomer and a dimer. In CHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 105 publications
5
21
0
Order By: Relevance
“…It showed two signals, with g = 2.003 and 1.994 but no hyperfine splitting, confirming the presence of an unpaired ring-electron in 1 -. The presence of two signals is consistent with a mixture of radical-containing products, which may feature aggregation of 1with either 1 2or residual 1 (as supported by the UV-visible data); such mixed-valent aggregated species and their similar EPR spectra were recently reported in detail for a ring-oxidized PcZn-based system [36].…”
Section: <Figure #3>supporting
confidence: 80%
“…It showed two signals, with g = 2.003 and 1.994 but no hyperfine splitting, confirming the presence of an unpaired ring-electron in 1 -. The presence of two signals is consistent with a mixture of radical-containing products, which may feature aggregation of 1with either 1 2or residual 1 (as supported by the UV-visible data); such mixed-valent aggregated species and their similar EPR spectra were recently reported in detail for a ring-oxidized PcZn-based system [36].…”
Section: <Figure #3>supporting
confidence: 80%
“…These two forms have been shown to possess different absorption spectra in the near-infrared (NIR) region. In particular, it has been demonstrated that the monomeric phthalocyanine cation radical has a Q -band centered at around 820–840 nm, while the diamagnetic dimer is associated with a Q -band centered around 715–730 nm and a broad NIR band observed at ∼1000 nm. , In addition, both the monomer and dimer have absorption at ∼500 nm (fingerprint band) and a set of transitions identified by UV–vis spectroscopy for [(Im)­ZnPc] +• at ∼420, ∼380, ∼330, and ∼286 nm. …”
Section: Introductionmentioning
confidence: 99%
“…Of the few fully characterized examples of meso‐protonated PcMs, two have been PcZn complexes, including a study by Kobayashi, et. al ., of a 1,4,8,11,15,18,22,25‐octaphenylphthalocyaninium zinc chloride complex, as well as our recent report of an unsubstituted PcZn complex protonated at the meso‐N as a result of hydrogen atom transfer between dimethoxyethane and a ring‐oxidized [Pc −1 Zn] .+ to form zinc phthalocyaninium tetrakis(pentafluorophenyl)borate [31,32] . The latter of these two remains the only reported example of an unsubstituted PcM protonated at the meso ‐N, with all others using ligand functionalization to increase the stability of the bound cations.…”
Section: Introductionmentioning
confidence: 64%
“…Beyond functional groups on the periphery or metals within the Pc‐core, the addition of protons to the meso‐nitrogen of the N 8 C 8 aromatic ring has been shown to strongly decrease the energy of the LUMO and red‐shift the Q‐band and B‐band absorptions [25,26] . Though the addition of strong acids to PcM complexes has been shown to produce mono, di, tri and tetra meso ‐protonated complexes in solution, few of these species have been isolated and structurally characterized [27–32] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation